Blepharisides A and B, new flavonol glycosides from Blepharis ciliaris growing in Saudi Arabia. (March 2015) - Mohamed, Gamal A.; Ibrahim, Sabrin R.M.; Elkhayat, Ehab S.; Ross, Samir A.; Sayed, Hanaa M.; El-Moghazy, Safaa A.M.; El-Shanawany, Mohamed A.
Graphical abstract: Highlights: The MeOH extract of Blepharis ciliaris aerial parts was investigated. Two new and one known compounds were isolated. Their structures were established by different spectroscopic analyses. Hepatoprotective activity of the MeOH extract and its fractions was estimated. The antioxidant and anti-inflammatory activities of the isolated compounds were evaluated. Abstract: Bio-guided fractionation of the total MeOH extract (TME) of the aerial parts of Blepharis ciliaris (L.) B.L. Burtt. (Acanthaceae) growing in Saudi Arabia was carried out to evaluate its hepatoprotective activity against CCl4 -induced hepatotoxicity in rats. Successive chromatographic separations of the potent hepatoprotective n -BuOH fraction afforded two new flavonol glycosides, blepharisides A (1 ) and B (2 ), along with quercetin 3- O -rutinoside (3 ). Their structures were established by UV, IR, 1D, 2D NMR, and HRESIMS spectral data, in addition to comparison with literature data. Co-treatment of CCl4 hepatic injured rats with the total MeOH extract (TME) and its fractions significantly restored the hepatic marker enzymes and total bilirubin to near-normal values compared to silymarin (reference drug). The isolated compounds were evaluated for their antioxidant and anti-inflammatory activities. They displayed significant antioxidant activity (DPPH assay) in relation to propyl gallate (positive control) (% inhibition of 88.2, 87.9, and 74.2, respectively). Compounds1 and2 demonstrated anti-inflammatory effects in the carrageenin induced paw edema method at a dose of 10 mg/kg.